Addressing oral health barriers to care in head and neck cancer patients using a novel collaborative care approach - Matthew D. Greaves (Wiley, 2021)
Abstract With appropriate interprofessional collaboration, dental schools have the capacity to facilitate the dental management of patients with head and neck cancer who are facing multiple barriers to care.